2013
DOI: 10.1016/j.asjsur.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic approach for the treatment of right colon cancer: A technical critique

Abstract: Our preliminary data indicate that TLRC could result in better outcomes for right colon cancer patients than LARC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The term laparoscopic-assisted colectomy encompasses procedures in which a variable portion of the dissection and mobilization is performed intracorpor eally followed by exteriorization of the bowel for the extracorporeal anastamosis (EA). 3,4,10 Alternatively, a totally laparoscopic colectomy refers to a procedure in which the entire mobilization, resection and anastamosis is performed intracorporeally (IA) before specimen extraction. 3,4,10 We sought to compare the short-term outcomes of LRHC using either an IA or EA technique.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The term laparoscopic-assisted colectomy encompasses procedures in which a variable portion of the dissection and mobilization is performed intracorpor eally followed by exteriorization of the bowel for the extracorporeal anastamosis (EA). 3,4,10 Alternatively, a totally laparoscopic colectomy refers to a procedure in which the entire mobilization, resection and anastamosis is performed intracorporeally (IA) before specimen extraction. 3,4,10 We sought to compare the short-term outcomes of LRHC using either an IA or EA technique.…”
mentioning
confidence: 99%
“…[1][2][3] Laparoscopy has the additional benefits of improved postoperative recovery, reduced analgesia requirements and shorter length of hospital stay. 2,[4][5][6] There is also evolving evidence for long-term benefits, including reduced bowel obstructions and ventral hernias. 4,[7][8][9] There is wide variation among laparoscopic colon resection techniques, including the approach for mobilization (medial-to-lateral v. lateral-to-medial) and the extent of intracorporeal vessel ligation, bowel division or anastamosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Francesco Roscio et al thought that totally laparoscopic surgery would be an ideal treatment for patients with higher BMI, because it prevented extensive incisions for the extraction of large specimens through very thick abdominal walls and reduced the risk of microlacerations during the exteriorization of heavy and short mesenteries [11]. Ilknur Erguner et al thought that totally laparoscopic surgery avoided ischemia-reperfusion of the colon during extracorporeal anastomosis for a minimum of 5-10 min and provided a free specimen extraction site such as suprapubic incision or the natural orifices, which would offer less adhesions, less incisional hernia, and better cosmesis [12]. Our previous studies also found that totally laparoscopic surgery for colon cancer had the advantages of less postoperative pain and earlier time to first flatus, which promises a safe and feasible procedure with satisfactory short-term outcomes [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Francesco Roscio et al thought that totally laparoscopic surgery would be an ideal treatment for patients with higher BMI, because it prevented extensive incisions for the extraction of large specimens through very thick abdominal walls and reduced the risk of microlacerations during the exteriorization of heavy and short mesenteries [11] . Ilknur Erguner et al thought that totally laparoscopic surgery avoided ischemia-reperfusion of the colon during extracorporeal anastomosis for a minimum of 5-10 min and provided a free specimen extraction site such as suprapubic incision or the natural orifices, which would offer less adhesions, less incisional hernia, and better cosmesis [12] .…”
Section: Postoperative Recovery and Complicationsmentioning
confidence: 99%